EMPLOYING TASK BASED LEARNING APPROACH IN ENGLISH TEACHING IN GOOGLE CLASSROOM - Hanip Pujiati; Muchlas Suseno; Lasito Lasito (PINISI :Journal of Teacher Professional, 2022)
The internet-based learning platforms such as Google Classroom have been widely used by teachers to support process of teaching and learning. However, there was not enough study which investigate the use of Google Classroom before and while Corona virus pandemic. This current research aims to explore the use of Google Classroom application in EFL classes particularly those that employ Task Based Language Teaching and Learning. Qualitative  Descriptive  Analysis  was  utilized  for  the  current  research  in  a  way  the implementation of Google Classroom-based teaching and learning could be investigated. There were 40 teachers High Schools from various schools in Indonesia and Sekolah Indoesia Jeddah participated in this study as they were known to use the platform for their classes. It was found that teachers applied Google  Classroom  based  on  Task  Based  Learning  with  a  certain  level  of  creativity  in composing various kinds of assignments and organising the assignments properly for assessing listening, speaking, reading and writing. Teachers provided feedback regularly in Google Classroom while more traditional face-to-face feedback was still given to students.  Teachers established communication by giving comments, correcting students’ work, and explaining the materials. Students showed a positive response as they were involved in the online learning activity. The learning application was of their interest as they found it relatively new yet suitable for their learning needs. The learning application was of their interest as they found it relatively new yet suitable for their learning needs. Both teachers and students encountered technical problems related to the internet connection during the use of Google Classroom application. Most teachers and students found it difficult in operating this application properly since they were not familiar with the learning tool.  On the other hand, some students  were less-equipped in terms of access to smartphones smartphone to access Google Classroom that they worked collaboratively with their friends and shared a same Google account for task submissions.